PsycEXTRA Dataset 2004
DOI: 10.1037/e722842011-002
|View full text |Cite
|
Sign up to set email alerts
|

An empirical test of gain-loss separability in prospect theory

Abstract: We investigate a basic premise of prospect theory, that the valuation of gains and losses is separable. In prospect theory, gain-loss separability implies that a mixed gamble is valued by summing the valuations of the gain and loss portions of that gamble. Two experimental studies demonstrate a systematic violation of the double matching axiom, an axiom that is necessary for gain-loss separability. We document a reversal between preferences for mixed gambles and the associated gain and loss gambles-mixed gambl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
39
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 60 publications
2
39
0
Order By: Relevance
“…Intuitively, if you prefer the good part of B to the good part of A, and if you prefer the bad part of B to the bad part of A, then you should prefer B to A. Wu and Markle (2005) devised a test from a choice in Levy and Levy (2002, Experiment 2), shown in Choice Problems 12.1, 12.2, and 12.3 in Table 5. Wu and Markle (2005) found that the majority prefers B ϩ ՝ A ϩ and B Ϫ ՝ A Ϫ ; however, the majority does not prefer B ՝ A, contrary to CPT/RSDU and any model that satisfies gain-loss separability, including OPT.…”
Section: Violations Of Gain-loss Separabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Intuitively, if you prefer the good part of B to the good part of A, and if you prefer the bad part of B to the bad part of A, then you should prefer B to A. Wu and Markle (2005) devised a test from a choice in Levy and Levy (2002, Experiment 2), shown in Choice Problems 12.1, 12.2, and 12.3 in Table 5. Wu and Markle (2005) found that the majority prefers B ϩ ՝ A ϩ and B Ϫ ՝ A Ϫ ; however, the majority does not prefer B ՝ A, contrary to CPT/RSDU and any model that satisfies gain-loss separability, including OPT.…”
Section: Violations Of Gain-loss Separabilitymentioning
confidence: 99%
“…Wu and Markle (2005) devised a test from a choice in Levy and Levy (2002, Experiment 2), shown in Choice Problems 12.1, 12.2, and 12.3 in Table 5. Wu and Markle (2005) found that the majority prefers B ϩ ՝ A ϩ and B Ϫ ՝ A Ϫ ; however, the majority does not prefer B ՝ A, contrary to CPT/RSDU and any model that satisfies gain-loss separability, including OPT. This example is consistent with the TAX model, with the simplifications listed in the note of Table 5, including the use of just one ␦ and u(x) ϭ x.…”
Section: Violations Of Gain-loss Separabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows application of ESAM with zero target to a set of experiments from Wu and Markle (2008). For comparison, we also show application of the entropic satisficing measure (Brown and Sim 2009;see Example 3) with zero target to these choices.…”
Section: Gain-loss Separabilitymentioning
confidence: 99%
“…For act f , the notation f + denotes the act f + s = max f s 0 for all s ∈ S, i.e., the gain part of the act, and the notation f − denotes the act f − s = min f s 0 for all s ∈ S, i.e., the loss part of the act. Wu and Markle (2008) show violations of gainloss separability by finding experimental violations of double matching. Double matching is the requirement f + High ∼ f + Low and f − High ∼ f − Low ⇒ f High ∼ f Low , and is a necessary requirement for gain-loss separability (thus violations of double matching are even stronger than are violations of gain-loss separability).…”
Section: Gain-loss Separabilitymentioning
confidence: 99%